2012
DOI: 10.1007/s10654-012-9718-2
|View full text |Cite
|
Sign up to set email alerts
|

Television habits in relation to overweight, diet and taste preferences in European children: the IDEFICS study

Abstract: Early television exposure has been associated with various health outcomes including childhood obesity. This paper describes associations between patterns of television viewing, on one hand, and diet, taste preference and weight status, on the other, in European preschoolers and schoolchildren. The IDEFICS baseline survey was conducted at examination centers in Italy, Estonia, Cyprus, Belgium, Sweden, Germany, Hungary, and Spain. 15,144 children aged 2–9 completed the basic protocol, including anthropometry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(129 citation statements)
references
References 17 publications
7
113
0
7
Order By: Relevance
“…Kristiansen et al (2013) suggested that a higher academic background of the parents was associated with a smaller amount of time spent watching TV; lower frequency of watching TV in the child's bedroom; greater amount of exercise; consumption of more fruits and vegetables, fewer sweets and less soft drinks and fast food and with more regular meals. Children's propensities to consume high-fat and high-sugar foods were positively associated with high-risk television behaviours (Lissner et al, 2012). Our previous study suggested that children's preferences were related to enjoying the school lunch (Osera et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…Kristiansen et al (2013) suggested that a higher academic background of the parents was associated with a smaller amount of time spent watching TV; lower frequency of watching TV in the child's bedroom; greater amount of exercise; consumption of more fruits and vegetables, fewer sweets and less soft drinks and fast food and with more regular meals. Children's propensities to consume high-fat and high-sugar foods were positively associated with high-risk television behaviours (Lissner et al, 2012). Our previous study suggested that children's preferences were related to enjoying the school lunch (Osera et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…However, these types of studies lack definite conclusions regarding cause and effect. 46,117,140,[181][182][183][184] On the other hand, while longitudinal studies follow children for a period of time, these types of studies may be limited by the use of retrospective data, parent-based reporting, limited measurements of other covariates, imperfect or missing measurements of confounders, gaps in data reporting, or selection bias. 165,185,186 Crosscomparison studies may prove difficult due to varying study designs and ages of the children.…”
Section: Discussionmentioning
confidence: 99%
“…In another approach, we calculated the propensity of children to favourably consume sweet or fatty foods in order to investigate the association between overweight, TV consumption and the adherence to an unhealthy food pattern [15]: The weekly consumption frequencies of each of 17 foods and beverages that are high in fat and of 12 foods and beverages with high sugar content were calculated for each of these categories. The other 14 items of the FFQ were also converted into weekly frequency scores.…”
Section: Correlates and Consequences Of Sensory Taste Preferencesmentioning
confidence: 99%